Vapor phase polymerization of 3,4-ethylenedioxythiophene on flexible substrate and its application on heat generation - Yang, Xiaoming; Shang, Songmin; Li, Liang; Tao, Xiao-Ming; Yan, Feng (Polymers for advanced technologies, 2011)
An oxidative chemical vapor phase polymerization process is applied to coat flexible polyethylene terephthalate (PET) fabrics with a uniform poly(3,4‐ethylenedioxythiophene) (PEDOT) film. This vapor phase polymerization method is a solventfree technique, which could yield a low resistance in the PEDOT‐coated PET fabric. The resistance as low as 52 Ω square−1 is achieved. The polymerization conditions, such as the concentration of oxidant, reaction time, and temperature, have been systematically investigated. The coated fabric samples exhibit an increase in temperature when subjected to a fixed DC voltage. This result indicates a potential application of these PEDOT‐coated fabrics as electric heating materials. Copyright © 2009 John Wiley & Sons, Ltd.